2019
DOI: 10.4103/idoj.idoj_253_18
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus pigmentosus: A clinico-etiological study

Abstract: Introduction: Lichen planus pigmentosus (LPP) is a distinct clinical entity commonly encountered in the Indian population. Aim: To study the clinicoetiological profile of LPP at a tertiary care hospital. Methods: A total of 100 patients with clinically and histopathologically confirmed diagnosis of LPP were included. Demographic details including the age of onset, duration of disease, symptoms, and family history were obtained. History regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(51 citation statements)
references
References 13 publications
1
50
0
Order By: Relevance
“…Histopathologic features include epidermal atrophy, vacuolar degeneration of the basal layer of the epithelium, perivascular lymphohistiocytic infiltrate in the upper dermis, and scattered dermal melanophages, 41,42 different from the typical LP in which melanin pigmentation is seen in the basal layer and extends to the upper part of lamina propria. 43 Although not common, oral mucosa can also be affected, 39 but our patient did not have OLP pigmentous.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Histopathologic features include epidermal atrophy, vacuolar degeneration of the basal layer of the epithelium, perivascular lymphohistiocytic infiltrate in the upper dermis, and scattered dermal melanophages, 41,42 different from the typical LP in which melanin pigmentation is seen in the basal layer and extends to the upper part of lamina propria. 43 Although not common, oral mucosa can also be affected, 39 but our patient did not have OLP pigmentous.…”
Section: Discussionmentioning
confidence: 55%
“…38 It usually occurs in women, aged 18–54 years. 39 The areas commonly affected are those frequently exposed to the sun, such as face and neck, followed by the trunk. 40 Most lesions are asymptomatic but there is usually an esthetic concern, 38 which was a complaint also reported by our patient.…”
Section: Discussionmentioning
confidence: 99%
“…10 The reccurance of blaschkoid lichen planus can be related to pregnancy. 11 Various treatments like tacrolimus, glycolic acid, hydroquinone have been tried in literature. 12 Tacrolimus is found to decrease pigmentation in LPP.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few reports on paraphenylene diamine induced beard dermatitis, 2,3 but to our knowledge, this is the first case report of a beard hair growth oil causing LPP. While hair colouring of the beard has been associated with LPP or other lichenoid eruptions, 4,5 hair growth oils have not been extensively studied yet. While studies have suggested the probable role of allergens/cosmetics in causing LPP on face, 6 given the heterogenous nature of the products that are classed as beard oils, data on specific triggers is largely unavailable as yet.…”
Section: Discussionmentioning
confidence: 99%